Perlindungan Hukum Pemilik Objek Jaminan yang Dibebani Hak Tanggungan Terhadap Lelang Eksekusi - Nirasnina Alya Usman; Eko Rial Nugroho (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2024)
Complex economic growth in Indonesia is increasingly needed to support people's lives, one of the method is through credit to channel funds from banks to the people. The credit granthing as the main agreement s a high risk action, so that a guarantee is required as an additional agreement for the legal protection of creditor. The process of implementing credit agreements does not always in the good way. However, legislation does not yet cover everything regarding explicit legal protection for resolving disputes that arise for various part inside and outside the credit agreement who are disadvantaged by the execution of mortgage guarantees due to bad credit. This research aims to find out the form of legal protection for owners of mortgage objects who do not provide approval in the credit agreement and the legal remedies that can be taken by owners of mortgage objects if they are harmed by a credit agreement and legal efforts that can be taken. The research method used in this writing is normative juridical with a statutory and conceptual approach. Data sources come from primary data and secondary data using library study data collection techniques. The resulting research is that legal protection has not been regulated explicitly and evenly for various part inside and outside the credit agreement who are harmed if the debitor breaches their contract resulting in bad credit with the execution of the mortgage guarantee, and the cancellation of the auction has not been clearly regulated if this has occurred. the process of executing the mortgage guarantee auction. Legal efforts that can be taken by the owner of the collateral object who suffers loss from the execution of the auction of mortgage collateral is by filed a resistance with the district court.